Influence of dimension stones on the increase of radon gas levels indoors - Amaral, P. G Q; Artur, A. C. [UNESP]; Bonotto, D. M. [UNESP]; Galembeck, T. M B [UNESP] (Trans Tech Publications, 2015)
The present work features results on the possible increase of radioactive 222Rn gas in environments of human habitation, caused by the use of dimension stones inside constructions with poor air circulation. For the study, granitic stones were selected from Espirito Santo and Minas Gérais states, commonly used as decorative stones and as wall covering. They were subjected to pétrographie analysis, determination of physical indexes and level of U, and were monitored to 238 quantify the amount of 222Rn gas released. The rates of 238U in the rocks stood between 2.9 ppm and 37 ppm, and the amount of 222Rn gas released ranged between extremely low for six of the stones (up to 98 Bq/m3) and moderate to considerably high (between 471 and 2483 Bq/m3) for four others. From the calculations to cumulatively evaluate the radiation levels generated by radon release, nine samples are below the limit of 4 pCi/L set by the EPA-Environmental Protection Agency (U.S.A.) and one is above that limit, demonstrating the role of these stones in increasing radon levels in ill-ventilated environments.
Keywords: Dimension stones; Indoor contamination; Radioactivity; Radon gas